REDESAIN IDENTITAS MEREK UNTUK MENINGKATKAN KESADARAN MEREK OCHA KITCHEN DI KOTA MALANG - Simajaya, Henry Himawan; Nirwana, Aditya; Pramudya, Bintang (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a fundamental pillar of the national economy, playing a crucial role in creating employment and distributing prosperity within society. Design plays a vital role in developing an effective visual identity through the creation of a Standard Guide Manual, which includes graphic design elements such as logos, packaging, and other components. Rebranding, which encompasses both evolutionary and revolutionary approaches, aims to establish a new image for a brand. Ocha Kitchen, an MSME in the culinary sector located in Malang, faces marketing challenges due to its diverse product range. To address this issue, a rebranding strategy is necessary, including the development of a sub-brand to focus on key products and enhance market competitiveness. Through effective rebranding, Ocha Kitchen is expected to improve its brand identity and marketing effectiveness, thereby attracting more consumer attention and meeting their needs. To achieve this, the Moser design methodology was utilized, resulting in a sub-brand called Baked Bliss, which focuses on cookies and includes the creation of a Guide Standard Manual Book and its related materials.